Diagnostic utility of hematological and biochemical markers for cystic echinococcosis in Tibetan patients of Sichuan, China - Ma, Meng; Yan, Hao; Shen, Liang; Zhang, Chongwei; Long, Juan (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis hospital-based case-control study aims to evaluate hematological and biochemical markers for the diagnosis of cystic echinococcosis (CE) in the Tibetan population of Sichuan.MethodsThis study involved 83 patients diagnosed with CE and 45 healthy controls. Diagnosis of CE was confirmed through antibody and imaging tests, followed by an analysis of differences in blood and biochemical markers.Results(1) Patients with CE displayed significant abnormalities in blood and biochemical indicators compared to healthy subjects, including increased levels of platelet count, eosinophil percentage, basophil percentage, prothrombin time, fibrinogen, activated partial thromboplastin time, total bilirubin, direct bilirubin, γ-glutamyltransferase, aspartate aminotransferase, and alkaline phosphatase. Conversely, there was a decrease in lymphocyte percentage, hemoglobin concentration, mean corpuscular volume, and hematocrit. (2) Prothrombin time levels were markedly elevated beyond normal reference values, with prolonged prothrombin time identified as a significant predictor for CE. (3) The area under the receiver operating characteristic curve (AUC) for predicting CE based on prothrombin time was 0.969, while the AUC for predicting CE using a combination of prothrombin time and eosinophil percentage was 0.982.ConclusionProlonged prothrombin time serves as a crucial indicator for CE, and its combination with eosinophil percentage significantly improves diagnostic accuracy, offering a potentially useful screening strategy in resource-limited endemic regions.